Measurements of bone mineral density in the lumbar spine and proximal femur using lunar prodigy and the new pencil-beam dual-energy X-ray absorptiometry - Choi, Dongil; Kim, Deog-Yoon; Han, Chung Soo; Kim, Seonwoo; Bok, Hae Sook; Huh, Wooseong; Ko, Jae-Wook; Hong, Sung Hwa (Skeletal radiology, 2010)
Objective We evaluated the correlation of the absolute bone mineral density (BMD) values of the lumbar spine and standard sites of the proximal femur obtained from a Lunar Prodigy and the newly developed pencil-beam dual-energy X-ray absorptiometry (Dexxum). Materials and methods Between June 2008 and December 2008, 79 Korean volunteers were enrolled. Measurements were obtained on the same day using both densitometers. The absolute BMD values (g/cm 2 ) from the two densitometers were evaluated using Pearson’s correlation analysis with Bonferroni’s correction for the three clinically important sites. In order to evaluate precision, we performed duplicate Dexxum measurements, and calculated the within-subject coefficient of variation (WSCV). Results The Pearson’s correlation coefficient (r) of BMD values for the total proximal femur, femoral neck, and lumbar spine by the two densitometers were 0.926, 0.948, and 0.955 respectively, and the null hypotheses of r = 0.8 were all rejected ( p < 0.001 by one-sided Z-test with Fisher’s z-transformation for each site). The T-scores ( r ≧ 0.842) and Z-scores ( r ≧ 0.709) also showed strong positive correlations. The duplicate BMD values of Dexxum showed a high level of precision (WSCV ≦ 4.27%). Conclusion Dexxum measurements of BMD, T-scores, and Z-scores showed a strong linear correlation with those measured on Lunar Prodigy.